2017
DOI: 10.1038/nm.4315
|View full text |Cite
|
Sign up to set email alerts
|

Marginal zone B cells control the response of follicular helper T cells to a high-cholesterol diet

Abstract: Splenic marginal zone B (MZB) cells, positioned at the interface between circulating blood and lymphoid tissue, detect and respond to blood-borne antigens. Here we show that MZB cells in mice activate a homeostatic program in response to a high-cholesterol diet (HCD) and regulate both the differentiation and accumulation of T follicular helper (T) cells. Feeding mice an HCD resulted in upregulated MZB cell surface expression of the immunoregulatory ligand PDL1 in an ATF3-dependent manner and increased the inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
138
3
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(153 citation statements)
references
References 57 publications
11
138
3
1
Order By: Relevance
“…Tfh cells mutually interact with B cells contributing for high‐affinity antibody production in plasma cells . Additionally, recent studies have demonstrated that specific regulatory B cells dampen Tfh differentiation through their elevated PDL1 expression in the B‐cell marginal zone, our data demonstrate this function, as the higher frequency of PDL1 high B cells was accompanied by a reduced differentiation of Tfh cells in the spleen. However, in the MLNs the low frequency of regulatory B cells (CD19 + CD40 + PDL1 high ) did not result in a higher Tfh cell differentiation, possibly due to the regulatory profile of the interacting‐DCs (CD11c + MHCII + PDL1 + ).…”
Section: Discussionsupporting
confidence: 70%
“…Tfh cells mutually interact with B cells contributing for high‐affinity antibody production in plasma cells . Additionally, recent studies have demonstrated that specific regulatory B cells dampen Tfh differentiation through their elevated PDL1 expression in the B‐cell marginal zone, our data demonstrate this function, as the higher frequency of PDL1 high B cells was accompanied by a reduced differentiation of Tfh cells in the spleen. However, in the MLNs the low frequency of regulatory B cells (CD19 + CD40 + PDL1 high ) did not result in a higher Tfh cell differentiation, possibly due to the regulatory profile of the interacting‐DCs (CD11c + MHCII + PDL1 + ).…”
Section: Discussionsupporting
confidence: 70%
“…We, therefore, performed detailed flow cytometry phenotyping of B cell subsets in bone marrow, spleen, and peritoneum, including peritoneal B1 cells and splenic marginal zone B cells that are known to regulate atherosclerosis. 13,33,41 There were no differences in bone marrow B cell fractions in Ldlr…”
Section: /Xbp1mentioning
confidence: 91%
“…[25][26][27] We and others have shown follicular B2 cell interactions with CD4 + T cells, antagonized by marginal zone B2 cells, promote pathogenic T cell responses in the atherosclerotic setting. [28][29][30][31][32][33] Few models have, therefore, addressed the specific role of antibodies in isolation without impacting on other B cell functions. Altogether, it is hard to predict the …”
Section: Meet the First Author See P 198mentioning
confidence: 99%
“…Consistent with this concept is the finding that deficiency of PD-1 or PD-L1 in high fat-diet-fed Ldlr -/- mice enhances lesion development and plaque inflammation compared with baseline lesion development in wild-type mice that occurs despite the presence of PD-L1 (Lichtman, 2012). Similarly, a recent study shows that hypercholesterolemia induces PD-L1 expression on marginal zone B cells, which inhibits pro-atherogenic T follicular helper cell responses (Nus et al, 2017). …”
Section: Energy Metabolism Affects Immune Cell Function In Atherosclementioning
confidence: 97%